Safety Risk Assessment of 3D Concrete Printing on Construction Sites - Abouzeid, Youssef Khaled (2025)
A Master of Science thesis in Construction Management by Youssef Khaled Abouzeid entitled, “Safety Risk Assessment of 3D Concrete Printing on Construction Sites”, submitted in July 2025. Thesis advisor is Dr. Adil Tamimi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).